Pengaruh Kualitas Produk, Harga, dan Strategi Pemasaran Terhadap Daya Beli Masyarakat dengan Kepuasan Konsumen sebagai Variabel Intervening - Priscaya, Ulita; Widiastuti, C. Tri; Dharmaputra, M. Fadjar (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the influence of product quality, price, and marketing strategy on consumer purchasing power with customer satisfaction as a mediating variable. The research was conducted on customers of Bike A Holic Semarang using a quantitative approach. Data collection was carried out through the distribution of questionnaires to 228 respondents using purposive sampling. Data were analyzed using statistical software and the Structural Equation Modeling (SEM) method with a Partial Least Square (PLS) approach. The results indicate that product quality, price, and marketing strategy have a positive effect on customer satisfaction. Furthermore, customer satisfaction significantly influences consumer purchasing power. However, not all variables directly impact purchasing power; some influence it only through customer satisfaction as a mediating variable. These findings highlight the importance of enhancing customer satisfaction to optimize consumer purchasing power.